(untitled) (Journal of actual problems of jurisprudence, 2018)
In this paper, the author discussed the sources of environmental information. Access to information, public participation in decision-making and access to justice is guaranteed by the Constitution of the Republic of Kazakhstan. The implementation of the constitutional right to receive, store and disseminate environmental information depends on the efficiency of collection and delivery of the latter. Key words: laws, regulations, access to environmental information, public, and environmental protection.